Empirical Analysis of Legal Regulations on Family Violence During Wartime in Ukraine: A Comprehensive Examination - Buriak, Kateryna; Prytula, Anatolii; Chorna, Maryna; Pyshna , Alla; Dolhov, Anton (Syariah: Jurnal Hukum dan Pemikiran, 2023)
This article focuses on examining family violence within the context of wartime conditions in Ukraine and proposes a criminological model for preventing such criminal offenses. The study reveals a significant surge in registered criminal offenses featuring domestic violence amidst the full-scale unprovoked invasion of Russia into Ukraine. Over a ten-month period in 2023, cases have risen by nearly 50% compared to the same period in 2022, with an average monthly increase of 27 recorded criminal offenses in 2023 compared to 2021. The heightened levels of stress, displacement of families, and the return of traumatized combatants contribute to an increase in domestic violence during and after war. This exacerbates incidents of physical, psychological, and sexual violence within households. The article addresses a critical scientific issue by advancing knowledge on family violence through a praxeological approach, aiming to identify solutions for fundamental and applied issues related to family protection in Ukraine. The study establishes that the Russian-Ukrainian war has elevated the frequency and severity of criminal offenses and instances of violence within the family sphere, necessitating a paradigm shift in the state's criminal-legal response to domestic violence perpetuated by offenders. The article systematically organizes achievements in countering and preventing family violence, synthesizes law enforcement and public practices in Ukraine and globally, and justifies directions for differentiating and individualizing punishment for perpetrators of family violence.